Effects of Drought Stress at the Booting Stage on Leaf Physiological Characteristics and Yield of Rice - Xiaolong Yang; Xiuxiu Wang; Yang Li; Lantian Yang; Long Hu; Yuling Han; Benfu Wang (Plants)
Drought stress is a major environmental constraint that limits rice (Oryza sativa L.) production worldwide. In this study, we investigated the effects of drought stress at the booting stage on rice leaf physiological characteristics and yield. The results showed that drought stress would lead to a significant decrease in chlorophyll content and photosynthesis in rice leaves, which would affect rice yield. Three different rice varieties were used in this study, namely Hanyou73 (HY73), Huanghuazhan (HHZ), and IRAT109. Under drought stress, the chlorophyll content of all cultivars decreased significantly: 11.1% and 32.2% decreases in chlorophyll a and chlorophyll b in HHZ cultivars, 14.1% and 28.5% decreases in IRAT109 cultivars, and 22.9% and 18.6% decreases in HY73 cultivars, respectively. In addition, drought stress also led to a significant decrease in leaf water potential, a significant increase in antioxidant enzyme activity, and an increase in malondialdehyde (MDA) content, suggesting that rice activated a defense mechanism to cope with drought-induced oxidative stress. This study also found that drought stress significantly reduced the net photosynthetic rate and stomatal conductance of rice, which, in turn, affected the yield of rice. Under drought stress, the yield of the HHZ cultivars decreased most significantly, reaching 30.2%, while the yields of IRAT109 and HY73 cultivars decreased by 13.0% and 18.2%, respectively. The analysis of yield composition showed that the number of grains per panicle, seed-setting rate, and 1000-grain weight were the key factors affecting yield formation. A correlation analysis showed that there was a significant positive correlation between yield and net photosynthetic rate, stomatal conductance, chla/chlb ratio, Rubisco activity, and Fv/Fm, but there was a negative correlation with MDA and non-photochemical quenching (NPQ). In summary, the effects of drought stress on rice yield are multifaceted, involving changes in multiple agronomic traits. The results highlight the importance of selecting and nurturing rice varieties with a high drought tolerance, which should have efficient antioxidant systems and high photosynthetic efficiency. Future research should focus on the genetic mechanisms of these physiological responses in order to develop molecular markers to assist in the breeding of drought-tolerant rice varieties.